Current Profiling of Research on Donkeys and Its Implications in Global Studies Based on Bibliometric Analysis - Almejnah, Othman; Saed, Hala A.; Marzok, Mohamed; Almubarak, Adel; Kandeel, Mahmoud; Shosha, Saad; El-khodery, Sabry; Farag, Alshimaa (Journal of Advanced Veterinary Research, 2023)
Tremendous work has been conducted in equine medicine research, with special reference to donkeys. Our study surveyed applied studies on donkeys by 2023 in a quantitative manner. Data were retrieved from the Web of Science database. The points investigated addressed the general criteria of global donkey research. Statistical data were set for each studied item using VOSviewer software, with a focus on the top ten results for each item. A total of 2947 documents were extracted. results revealed that author Burden F.A. had the highest number of published papers (68, 2.30%), publications in 2020 (8.92%) were at the front. The Egyptian Knowledge Bank (EKB) had the highest number of papers (177, 6.01%), the National Natural Science Foundation of China (Nsfc) (91, 3.08%) was the top funding agency, USA was the top nation in publications (13.87 %), and the majority of publications were in English (2757, 93.55 %). The highest publications in WOS categories, were collected from Veterinary Sciences (1695, 57.51%). Research articles were the most abundant form (85.61 %). Dairy and Animal Sciences was at the top of citation topics (351, 11.91%). Elsevier had the highest publications (23.58%), Journal of Equine Veterinary Science was placed in the top journals (163, 5.53%). The data from the current study can be used to assess the situation of applied research on donkeys, helping to set possible future maps.